Climate neutrality in the EU and China: An analysis of the stringency of targets and the adaptiveness of the relevant legal frameworks. Issue 3 (2nd August 2022) - Du, Haomiao; Zhang, Hao
Abstract: The European Union (EU) and China have committed to achieving net‐zero emissions by 2050 and 2060, respectively. To explore the legal nature of these objectives and how the legal frameworks support their delivery, this article assesses the stringency of objectives and the adaptiveness of relevant legal frameworks. The former compares the objectives' bindingness, scope, prescriptiveness and precision of such obligations and compliance mechanisms. The latter compares the dynamism of mitigation policies and the legal institutions and processes that promote decarbonization. The article concludes that the climate neutrality objective is enshrined in the EU's climate law framework with a high degree of stringency overall. By contrast, China mainly incorporates the targets into administrative measures, the cadre responsibility and evaluation system, lacking formal rules and robust enforcement. By accelerating legal reform to integrate carbon neutrality into relevant regulatory instruments and addressing implementation problems, China explores its distinctive pathway to delivering on the objective.